Akira Kurosawa's Stray dog - Hayasaka, Fumio 1914-1955 (<<The>> Criterion Coll., 2004)
A bad day gets worse for rookie detective Murakami when a pickpocket steals his gun on a hot, crowded bus. Desperate to right the wrong, he goes undercover, scavenging Tokyo's sweltering streets for the thief, whose desperation has led him to a life of crime. With each step, the cop and the criminal's lives become more intertwined and the investigation becomes an examination of Murakami's own dark side.
Bildformat 1.33:1 new high-definition digital transfer, with restored image and sound
Orig.: Japan 1949
Enth. audio commentary on "Stray dog" by Stephen Prince, author of "The warrior's camera: the cinema of Akira Kurosawa" ; a 32-minute documentary on "Stray dog" from the series "Akira Kurosawa: it is wonderful to create", including interviews with Kurosawa, production designer Yoshiro Muraki, actress Keiko Awaji, and others ; a 16-page booklet featuring Akira Kurosawa on "Stray dog", from his book "Something like an autobiography" and an essay by film critic Terrence Rafferty
Keywords: Tanteitachi - Nihon - Dorama; Detectives -- Japan -- Drama; Pickpockets -- Japan -- Drama; Japan -- Social conditions -- 1945- -- Drama; Feature films; Film noir; Foreign films; Gangster films; Motion pictures, Japanese; Videos (DVD)